Systemizace exotických opcí - Rejnuš, Oldřich (Vysoké učení technické v Brně, Fakulta podnikatelská, 2012)
Purpose of the article: „Exotic options“ are those sorts of optional instruments that, in terms of their properties, overtake restrictions of standard, so called „Plain Vanilla“ options, which means that they show „exotic properties“. With regard to the fact that they are stipulated, their versatility is practically unlimited, therefore their unanimous classification does not exist. The objective of this article is to outline suitable criteria for their basic division and, consequently, to create suitable method of system classification of exotic options in accordance with their characteristic specific properties. Methodology/methods: Proposed classification of exotic options is based on detailed analysis of their individual categories and on specification of their specific characteristic properties. Pursuant to knowledge, acquired in this way, they are systemized into individual groups and sub-groups. Scientific aim: This is an individual and therefore brand new way of possible systemization of exotic options. It is a multi-level open system, enabling to embody de facto all exotic optional instruments, including possible future ones. Findings: Pursuant to performed analysis of specific properties of individual kinds of exotic options, all evaluated optional instruments were divided into five theoretically defined basic groups and subsequently specified in details in accordance with their specific characteristics. Conclusions: Performed analysis proved that many various sorts of exotic options are being used in financial markets. Whereas they are more and more often used for creating various sorts of synthetic investment instruments (so called “structured products”), it seems to be clear that their number will be growing. It was proved though that criteria enabling their systemization can be defined. In the case given, these criteria are specific optional properties that enable creating comprehensive, open, multi-level system for exotic options, the presentation of which is the content of this article.
Exotic Options Systemization
Keywords: Plain Vanilla options; derivative instruments; structured products; Exotic options